Anxiety and depression during pregnancy in women and men - Teixeira, César (2009)
Background: High-anxiety and depression rates have been reported in women during pregnancy; however men and parity effects have not been studied as extensively. The purpose of this study was to analyze anxiety and depression in women and their partners during pregnancy, namely differences between the 1st, 2nd and 3rd pregnancy trimesters, between women and men, and between primiparous and multiparous. Methods: A sample of 300 women and their partners (n=560) were recruited during the 1st pregnancy trimester and have completed the STAI-S (State Anxiety Inventory) and the EPDS (Edinburgh Postnatal Depression Scale) in the 1st, 2nd and 3rd pregnancy trimesters. Results: Anxiety symptoms follow a U pattern in pregnancy, while depression symptoms decrease throughout pregnancy.Women show higher anxiety and depression values than men, although patterns of time variation are similar. Primiparous women and men display higher anxiety levels in the 1st than in the 3rd trimester, while multiparous register higher values in the 3rd than in the 1st pregnancy trimester. Conclusion: Different time variation in pregnancy was found for anxiety and depression symptoms; however anxiety and depression symptoms are particularly high during the 1st trimester. Intervention needs will be analyzed according to the results.